A laboratory course for programming with Java - Dale, Nell B. (Jones and Bartlett, 2003)
A Laboratory Course for Programming with Java actively engages students in the process of learning programming language concepts. Based on a proven teaching philosophy that emphasizes active learning, this manual provides 14 hands-on laboratory activities, each of which contains Prelab, In-lab, and Post-lab exercises. A perfect accompaniment to Programming and Problem Solving with Java , this lab manual is organized to correspond directly with the textbook. As students use these labs to apply their textbook knowledge, they develop a meaningful understanding of language concepts. Whether students use this laboratory in a supervised environment or for independent learning, they will benefit from the challenge and support that it provides.